Genre Studies on Popular Islamic Literature in Indonesia - M. Oky Fardian Gafari; Muhammad Hafidz Assalam; Wahyu Wiji Astuti (LingLit Journal Scientific Journal for Linguistics and Literature, 2022)
Religious values, especially Islam, have always been attractive themes in the preparation of literary works. Since the era of oral literature, to written literature, even digital literature as is currently happening, Islamic themes have always been a magnet for readers. In fact, since the spread of the era of ecranization, the nuances of darkness have also become a magnet for audiences in cinemas. From here then comes the term Popular Islamic Literature. Popular Islamic Literature is a differentiator from Islamic Literature which is noble and tends to be absurd. This article aims to reveal 1) The characteristics of popular Islamic literature that distinguish it from other genres, 2) The motives for the emergence of Popular Islamic Literature in Indonesia. The results obtained are that Popular Islamic Literature dominates the distinctive features which include practical Islamic naming code and fashion code. Islam is different from noble Islam which tends to be absurd and transcendental. The Popular Islamic Literature genre follows market tastes that place more emphasis on instant culture and visual beauty. The genre of Popular Islamic Literature will become an established genre if its authors, such as Helvi Tiana Rosa, Habiburahman El-Syirazy, Asma Nadia, Tere Liye and so on, remain productive in producing works with the same theme that are of interest to many readers.